Analisis Strategi Promosi Menggunakan Media Sosial Tiktok Dalam Memasarkan Produk Pada UMKM - Revita Sari (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research discusses the analysis of promotional strategies using social media Tik Tok, the type of research used is a qualitative method with observational data collection techniques, and documentation is carried out to obtain data. The focus of this research is what promotional strategies should be carried out by MSME Baso Aci Ganteng through social media tick tock? The research results show that Baso Aci Ganteng wants to make TikTok a media or promotional tool to communicate products and sales activities carried out by Baso Aci Ganteng, where currently TikTok is a media that almost everyone has, from children to adults.